(untitled) (Proceedings of the International Conference on Public Health, 2017)
Leprosy ,one of negledted tropical diseases, is a contagious disease that is so feared by all of people. It is still become one of the problems that faced by the world society because it can lead to a very complex problem. People who are suffering from leprosy may have disabilities that are settled if it does not get healing and handling well. As impact, lepers who had been leprosy deseas get some difficulties for instant, the anxiety to approach themselves into society, lost their social status progressively, isolated from family, friends, and society. therefore, the effort to avoid distabilty toward lepers is a self caring. Selfcare can prevent disability and encourage patient self-awareness to heals. It can be developed become a selfcare group that help lepers to support each other. Because there is a quote “camaraderie”. The method in this research is A cross-sectional study with 35 lepers was followed by a focus group discussion with fasilitator and health workers. The results of this research, that majority of lepers were women (68.6%), mostly aged 36-45 years (28.6%), 25 respondents (71.4%) followed self care group activities, 62.9% (22 respondents) have good confidence. Result of analysis with Chi-square test showed there was correlation between participation in self care group with confidence of leprosy patient p = 0,031, OR = 7,389 (CI 1,441-37,883). In focus group discussion , the members of self-care group stated that the self-care group had an important role in improving the confidence of leprosy patients through interaction and communication between each member, motivation and other activities. as conclusions, Self Care Group very helpful to increasing lepers’ confidence. Suggestion: This activity can be developed throughout the health centers in Jeneponto. Also expected cross-sectoral cooperation in the development of Self Care Group.